Peningkatan Kesadaran Anak Usia Sekolah Dalam Menjaga Kebersihan Lingkungan Melalui Pembuatan Bank Sampah di Pondok Pesantren Nashriyah NW Sekunyit, Desa Bunut Baok Kabupaten Lombok Tengah - Nur Azliana; Firman Ali Rahman; Baiq Yulia Hasni Pratiwi (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
Waste banks are an alternative waste management in Indonesia. This waste bank is one of the strategies for implementing 3R (Reuse, Reduce, Recycle) in managing waste at the source at the community level with an economic incentive pattern. This research aims to provide an understanding of waste banks for re-management and to classify types of waste. Apart from that, waste banks also play an important role in establishing a sustainable lifestyle through several discussions. First, the waste bank increases environmental awareness among the school environment, changes mindsets towards waste, and inspires behavioral changes towards a cleaner and more sustainable environment. Second, active community participation in waste banks strengthens citizen involvement in waste management and creates a participatory climate in environmental decision making. Third, waste banks open up local economic opportunities by creating products from waste, helping to empower the local community's economy, and reducing social inequality. Furthermore, waste banks reduce the use of new natural resources by processing used goods into useful products, helping to reduce pressure on the environment. The method used using practical guidance and counseling is a method where a group of people with problems (clients) are helped to feel and act more pleasantly by interacting with someone who is not troublesome. The guidance provided can increase students' creativity and motivation to protect the school environment and social environment.